2019
DOI: 10.1001/jamanetworkopen.2019.14171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combination l-Citrulline and Metformin Treatment on Motor Function in Patients With Duchenne Muscular Dystrophy

Abstract: Key PointsQuestionDoes treatment with l-citrulline and metformin combination therapy reduce motor function decline in ambulant patients with Duchenne muscular dystrophy?FindingsIn this randomized clinical trial of 47 ambulant male children aged 6.5 to 10 years with Duchenne muscular dystrophy, treatment with a combination of l-citrulline and metformin therapies provided a clinically relevant but not statistically significant reduction in motor function decline, as assessed by the transfer and standing posture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…It will therefore be very important in the near future to determine whether treatment with metformin can improve dystrophic cardiomyopathy in the advanced stage of the pathology. To conclude, our data support the concept that metformin alone or in combination with other drugs might be a potential therapeutic strategy to ameliorate the dystrophinopathies (Casteels et al, 2010 ; Ljubicic and Jasmin, 2015 ; Hafner et al, 2016 , 2019 ; Mantuano et al, 2018 ; Vitiello et al, 2019 ).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…It will therefore be very important in the near future to determine whether treatment with metformin can improve dystrophic cardiomyopathy in the advanced stage of the pathology. To conclude, our data support the concept that metformin alone or in combination with other drugs might be a potential therapeutic strategy to ameliorate the dystrophinopathies (Casteels et al, 2010 ; Ljubicic and Jasmin, 2015 ; Hafner et al, 2016 , 2019 ; Mantuano et al, 2018 ; Vitiello et al, 2019 ).…”
Section: Discussionsupporting
confidence: 82%
“…We here tested metformin, an antidiabetic drug with pleiotropic properties that are related to its mitochondrial effects (for review see Foretz et al, 2014 ; Vial et al, 2019 ). Long-term treatment with metformin has already demonstrated some beneficial effects on motor function in stable DMD patients with encouraging evidence regarding muscle degeneration and histopathology (Hafner et al, 2016 , 2019 ). The exact mechanisms of action of metformin have yet to be elucidated; however, at high doses, metformin inhibits the oxidation of NADH at the complex I level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro, metformin protected the myotubes from cardiotoxin induced degeneration [ 118 , 119 ]. A Phase I clinical trial (NCT02516085) completed in 2012 in Switzerland showed slowing of the disease process in DMD patients but no change in motor function [ 120 , 121 ]. Adiponectin is decreased in mdx mice and DMD patients [ 122 , 123 ] and is widely recognized as an insulin sensitizer.…”
Section: Activation Of the Cellular Pathways In Skeletal Muscle Cementioning
confidence: 99%